Revenue management for the hospitality industry
"The purpose of this book is to provide a core understanding of the fundamentals of revenue management, which ties into the larger picture of revenue strategy. Aims to provide an insightful look into Revenue Management. Intends to give students knowledge about hands on skills that revenue managers must master to maximize profit within their hospitality organization." --